Long-Term Remission of an Aggressive Sebaceous Carcinoma following Chemotherapy - Angela Orcurto; Béatrice E. Gay; Wendy Jeanneret Sozzi; Michel Gilliet; Serge Leyvraz (Karger Publishers, 2014)
Sebaceous carcinoma (SC) is an uncommon neoplasm manifesting itself either in the eyelid or extraocularly in the head and neck area. Surgery is the standard of care. Irradiation is rarely proposed as monotherapy but is frequently administered as an adjuvant regimen following surgical resection. There is no known strategy concerning chemotherapeutic treatment in highly aggressive recurrent - or metastatic - forms of the disease. Our patient presented with an aggressive SC of the scalp recurring after multiple excisions and local radiotherapy. Chemotherapy with 5-fluorouracil, cisplatin and docetaxel was then initiated; 4 cycles were administered, followed by capecitabine maintenance. Shortly after starting chemotherapy, dermal lesions had completely disappeared and radiological response could be seen. The patient experienced an extended period (>20 months) of complete remission. In this report, we show an excellent response of a highly aggressive SC after a combination of chemotherapy as for head and neck cancers.